Soil seed bank and floristic diversity in a forest-grassland mosaic in southern Spain (Journal of Vegetation Science, 2003)
Soil seed bank and floristic diversity were studied in a forest of Quercus suber, a forest of Quercus canariensis and a grassland, forming a vegetation mosaic in Los Alcornocales Natural Park, southern Spain. The soil seed bank was estimated by the germination technique. In each community patch, diversity, woody species cover and herbaceous species frequency was measured. Three biodiversity components – species richness, endemism and taxonomic singularity – were considered in the vegetation and the seed bank. Forest patches had a soil seed bank of ca. 11 200-14 100 seed.m–2 and their composition had low resemblance to (epigeal) vegetation. The grassland patch had a more dense seed bank (ca. 31 800 seed.m–2 ) and a higher index of similarity with vegetation, compared with the forests nearby. The complete forest diversity was 71-78 species on 0.1 ha, including 12-15 species found only in the seed bank; the grassland species richness was higher (113 species on 0.1 ha). We discuss the role of soil seed banks in the vegetation dynamics and in the complete plant biodiversity of the mosaic landscape studied.